Interpreting The Expansion of The Principles of Legality in The New Criminal Code and Its implications for Legal Certainty in The Progressive Legal Perspective - M.H, Hadi Purnomo, S.I.K.; MM, Bambang Slamet Riyadi. SH. MH. (International Journal of Membrane Science and Technology, 2023)
In the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code, the principle of legality is formulated differently from the basic idea of the colonial one. The Indonesian criminal law system adheres to the principle of legality with a prohibition on the use of analogical legal interpretation. The question is, what about our new Criminal Code? In this study, the type of legal research used was a sociological juridical approach. Primary data was obtained from data sources in the field. Secondary data was obtained from primary legal material of Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code and related laws and regulations, as well as from books and other legal research journals. Reforming criminal law with a balance between formal legality and material legality is expected to create a criminal system that considers justice and legal benefits in addition to legal certainty. Based on the findings, this can be concluded. The concept of balance as the basic idea of reforming criminal law in Indonesia is in accordance with the ideals of law and the character of the Indonesian who places a balance between individual interests and social interests, the state law and living law in society, as well as formal legality and material legality, so that the values shared by the Indonesian people as mandated by Pancasila can be implemented in a just law enforcement.